Structures of KEOPS bound to tRNA reveal functional roles of the kinase Bud32 - Samara Mishelle Ona Chuquimarca; Jonah Beenstock; Salima Daou; Jennifer Porat; Alexander F. A. Keszei; Jay Z. Yin; Tobias Beschauner; Mark A. Bayfield; Mohammad T. Mazhab-Jafari; Frank Sicheri (Nature Communications)
Abstract The enzyme complex KEOPS (Kinase, Endopeptidase and Other Proteins of Small size) installs the universally conserved and essential N6-threonylcarbamoyl adenosine modification (t6A) on ANN-decoding tRNAs in eukaryotes and in archaea. KEOPS consists of Cgi121, Kae1, Pcc1, Gon7 and the atypical kinase/ATPase Bud32. Except Gon7, all KEOPS subunits are needed for tRNA modification, and in humans, mutations in all five genes underlie the lethal genetic disease Galloway Mowat Syndrome (GAMOS). Kae1 catalyzes the modification of tRNA, but the specific contributions of Bud32 and the other subunits are less clear. Here we solved cryogenic electron microscopy structures of KEOPS with and without a tRNA substrate. We uncover distinct flexibility of KEOPS-bound tRNA revealing a conformational change that may enable its modification by Kae1. We further identified a contact between a flipped-out base of the tRNA and an arginine residue in C-terminal tail of Bud32 that correlates with the conformational change in the tRNA. We also uncover contact surfaces within the KEOPS-tRNA holo-enzyme substrate complex that are required for Bud32 ATPase regulation and t6A modification activity. Our findings uncover inner workings of KEOPS including a basis for substrate specificity and why Kae1 depends on all other subunits.